THE IMPACT OF PRICE AND FACILITIES ON EV PURCHASE INTENT THROUGH INNOVATIVE BEHAVIOR - Kurniawan, Hironimus Hari; Sidi, Agus Purnomo (Jurnal Apresiasi Ekonomi, 2025)
This study analyzes the influence of facilitating conditions and prices on the purchase intention of electric vehicles (EVs) in Indonesia by examining the mediating role of innovative behavior. Data from 362 respondents in six major cities were processed using PLS-SEM. The results show that facilitating conditions and prices directly and significantly influence buying intent, as well as influencing innovative behavior. Innovative behavior also has a significant effect on purchase intent. In the mediation test, innovative behaviors did not mediate the relationship between the facilitating conditions and the purchase intent. However, it significantly mediates the relationship between price and purchase intent. This indicates that prices influence buying intent indirectly through innovative behavior. The key implications are the need for a holistic marketing strategy that focuses on building a supporting ecosystem, as well as communicating long-term economic value to attract innovative consumers.